Dr. Thara Rangaswamy - G Madhu Vamsi (Telangana Journal of Psychiatry, 2022)
Dr. Thara is a one of the pioneer women psychiatrists in India. Along with Sarada Menon and S Rajakumar, she cofounded an nongovernmental organization, called Schizophrenia Research Foundation (SCARF), based in Chennai, India. She is currently the Vice Chairman of SCARF, which was previously held by Dr. Sarada Menon. She is a researcher in schizophrenia and community mental health. She is the editor of the book-Emergencies in Psychiatry in low- and middle-income countries. Her Madras Longitudinal Study which has followed up persons with first episode schizophrenia for 35 years and is one of its kinds in the world. She pioneered the use of mobile telepsychiatry to deliver high quality care for schizophrenia in resource-less rural communities. In 2022, she received the Nari Shakti Puraskar, the highest civilian award for women, for creating awareness for mental disorders.